Pinacol Coupling of Aromatic Aldehydes Using TiCl3-Al-H2O Under Ultrasound Irradiation - Lin, Zhi-Ping; Li, Ji-Tai; Li, Tong-Shuang (Letters in Organic Chemistry, 2006)
Titanium trichloride in H2O can be reduced by Al to the corresponding low valent titanium complexes, which can reduce some aromatic aldehydes and ketones to the corresponding pinacols in 15-83% yields within 25-100 min at r.t.under ultrasound irradiation.
Keywords: low valent titanium